Research Progress on the Influence of Intermittent Fasting on Cardiovascular Disease Risk Factors - CUI Yanru, CEN Qiuyu, WEI Juanfang, WANG Wenchun, ZHANG Anren (Zhongguo quanke yixue, 2022)
In recent years, the prevalence and mortality of cardiovascular diseases in China have shown a significant upward trend, cardiovascular disease has become a major disease endangering the health of Chinese residents. Intermittent fasting (IF) as a cyclical energy restriction dietary intervention has been proven to have a wide range of health benefits, which can reduce weight, improve glucose regulation, lower blood pressure and blood lipid levels, inhibit inflammation, so as to delay the occurrence and development of cardiovascular disease. Currently, researchers in China have paid insufficient attention to the potential role of IF in the prevention and treatment of cardiovascular diseases. This article reviews the effects and mechanisms of IF on cardiovascular disease risk factors such as dyslipidemia, obesity, diabetes and hypertension, in order to provide new ideas for the prevention and treatment of cardiovascular diseases. It is found that IF has potential application prospects in the prevention and treatment of cardiovascular diseases, which can be used to prevent and control the risk factors of cardiovascular disease, the IF-mediated metabolic benefits can be related to glucose-ketone body metabolic transformation, browning of white fat, autophagy pathway and remodeling of intestinal flora.